Bauweisenermittlung für eine Bauklasse S - Gerlach, Alexander; Hothan, Jürgen (Bundesminister für Verkehr, Abt. Straßenbau, 1989)
A determination of the useful life of various pavement types and an assessment of the effects of increases in axle loads on service life.
Zsfassung in dt., engl. und franz. Sprache
Keywords: Pavements -- Live loads; Service life (Engineering); Bemessung; Fahrbahnbefestigung; Verkehrsbelastung; Klassifikation